The association of age with the clinicopathological characteristics and prognosis of colorectal cancer: a UK single‐centre retrospective study. (30th October 2019) - Anele, C. C.; Askari, A.; Navaratne, L.; Patel, K.; Jenkin, J. T.; Faiz, O. D.; Latchford, A.
Abstract: Introduction: Colorectal cancer (CRC) is uncommon in patients under the age of 40 years and its association with poor histological features and survival is uncertain. This study aimed to evaluate age‐related differences in clinicopathological features and prognosis in patients diagnosed with CRC. Method: A single‐centre retrospective review of all patients diagnosed with CRC between 2004 and 2013 was performed. Patients were stratified into three age groups: (1) 18–40 years, (2) 41–60 years and (3)> 60 years. Clinicopathological characteristics and outcomes were compared between the three groups. Results: A total of 1328 patients were included, of whom 57.2% were men. There were 28 (2.1%) patients in group 1, 287 (21.6%) in group 2 and 1013 (76.3%) in group 3. Group 1 had the highest proportion of rectal tumours (57.1% in group 1, 50.2% in group 2 and 31.9% in group 3; P < 0.001). Tumour histology and disease stage were comparable between the groups. Group 1 had significantly worse disease‐free survival (DFS) than the two older groups (44%, 78% and 77%, respectively; P = 0.022). Multivariate analysis demonstrated that age was not an independent prognostic factor whereas Stage III disease [hazard ratio (HR) 4.42; 95% CI 2.81–6.94; P < 0.001] and neoadjuvant chemotherapy (HR 1.65; 95% CI 1.06–2.58; P = 0.026) were associated with increased risk of recurrence. Conclusion: Patients under the age of 40 are more likely to present with rectal cancer and have comparable histological features than the older groups. Despite higher rates of adjuvant and neoadjuvant treatment, the young group were found to have worse DFS.